Habitat Buatan Cumi Untuk Menunjang Konservasi dan Wisata Bahari Pantai Pangi, Blitar - Ali Muntaha; Sunardi Sunardi; Zainul Abidin; Sukandar Sukandar; Edriana Pangestuti; Eko Sulkhani Yulianto; Hanif Rafdhiansyah Insani; Fatrah Sulaeman Hutasuhut (Jurnal Pengabdian Masyarakat (abdira), 2022)
This community service activity for the Doctoral Serving UB funding scheme is one of the efforts to help partners in Pangi Beach in managing Pangi beach marine tourism. The activity will be held from June to November 2021 located on Pangi beach. There are three main activities, namely discussions with partners, designing and producing artificial squid habitats and finally setting up artificial squid habitats on the seabed of Pangi beach. The method implemented in this service is workshop, training, discussion and assistance starting from training to setting 4 artificial squid habitat units on Pangi beach which is carried out well. The results of the activities in addition to the installation of artificial squid habitats, are also the transfer of knowledge in conservation-based tourism management. The follow-up activity is monitoring which is planned to be carried out through Internship and Student Thesis Research activities in 2022. Cooperation and public awareness (partners) of the importance of developing conservation-based tourism are the main things for this service activity to run well.